MANAJEMEN PEMBELAJARAN E-LEARNING DALAM MENINGKATKAN EFEKTIVITAS BELAJAR SISWA DI SEKOLAH DASAR NEGERI 1 TANGGULANOM KECAMATAN SELOPAMPANG KABUPATEN TEMANGGUNG - Hedhi Antoro; Muhammad Prayito; Dyah Nugrahani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze in depth the implementation of e-learning-based learning management which includes planning, implementation, and evaluation. In addition, this study also identifies the driving and inhibiting factors of e-learning implementation and its implications for student learning effectiveness. The research approach used is qualitative with descriptive methods. Data were collected through in-depth interviews, direct observation, and document analysis. The subjects of the study included the principal, teachers, students, and parents of students at SD Negeri 1 Tanggulanom. The focus of the study was directed at the management of technological resources, teacher readiness, and learning strategies to support the success of e-learning. The results of the study indicate that the implementation of e-learning at SD Negeri 1 Tanggulanom has had a positive impact on learning effectiveness, as evidenced by a significant increase in students' literacy and numeracy skills, as well as school achievement at the district level. However, the implementation of e-learning faces several challenges, such as limited information and communication technology (ICT) infrastructure, resistance of some teachers to technology, and parental concerns about the impact of technology use on children. In terms of management, e-learning planning at this school involves identifying student needs, compiling digital-based materials, and training teachers to improve ICT competency. In the implementation stage, e-learning is carried out through a combination of online platforms and hardware such as tablets and projectors, supported by supervision by the principal. The evaluation showed significant progress in student learning outcomes, although there were still technical obstacles that needed to be overcome. This study recommends strengthening digital infrastructure, ongoing training for teachers, and increasing collaboration between schools and parents to support the sustainability of e-learning. This study also contributes to the development of technology-based learning models at the elementary education level.